Znanstveno pisanje: znanstveno pisanje ≥ razmišljanje v besedah - Aberšek, Boris; Kordigel Aberšek, Metka (University of Maribor Press, 2019)
Scientific Writing: Thinking in Words. Everything is easy, if only one knows how to do it! Scientific writing is no exception. To become a successful author of scientific and technical works, one must first adopt a positive attitude towards writing. The next step is to acquire the basic "skills of the trade" by internalizing basic guidelines, such as the IMRaD (Introduction, Methods, Results and Discussion) structure. Scientific writing is also a dynamic process and what one learned years ago, may no longer be valid. The format of writing may also vary from one journal to the next, from one publisher to the next. As an author of scientific writing, one must always follow and adopt to these different requirements. Only by being published and accepted by the readers, a study reaches its purpose – recognition in the world of scientific writing. To not dampen the spirits of future authors too much, we composed this handbook to make it short, but sufficiently comprehensive. We hope to have succeeded.